Biodegradable lung sealant

By developing a two-component, biodegradable, fast-coagulated liquid sealant composition, the multi-arm PEG polymer dissolves in different buffers and mixes immediately to form a highly adherent and elastic hydrogel, the problem of poor stratification and coverage caused by the existing lung sealant due to stiffness mismatch is solved, and an efficient and simplified lung sealing effect is achieved.

CN119816332APending Publication Date: 2025-04-11ETHICON INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380062715.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-15
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lung sealant causes shear stress due to the mismatch of stiffness when in contact with lung tissue, resulting in undesired stratification and poor coverage, and the application process is complicated and material waste is large.

Method used

A two-component, biodegradable, fast-coagulated liquid sealant composition is developed to form a highly adherent and elastic hydrogel by dissolving different models of multi-arm PEG polymers in alkaline and weakly acidic buffers and mixing immediately before application to tissues.

Benefits of technology

The sealant has high tensile strength, high elongation of break and low elastic modulus, and is suitable for lung seals that do not hinder the natural circulation of the lungs, significantly improving the sealing performance and simplifying the application process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005289797320000121
    Figure BDA0005289797320000121
  • Figure BDA0005289797320000131
    Figure BDA0005289797320000131
  • Figure HDA0005289797330000011
    Figure HDA0005289797330000011
Patent Text Reader

Abstract

The present invention relates to a rapid hardening liquid lung sealant that forms a highly adhesive and elastic hydrogel. Provided are lung sealants comprising two high molecular weight (20kDa) multi-arm PEG compositions wherein the first PEG composition comprises an alkaline buffer and the second PEG composition comprises a weakly acidic buffer for optimized cure times and extended working times. In some embodiments, PEG further comprises a radiation protective agent, such as tocopherol. In some embodiments, a colorant is added to one or both PEGs of the lung sealant to improve visualization of the lung sealant to human lung tissue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a two-component biodegradable sealant for sealing lung tissue and methods of using the same. Background Art

[0002] Tissue sealants are used as an auxiliary to primary lung pleural closure using, for example, sutures, surgical meshes and staples. There is currently no auxiliary hemostatic sealant used as a standard of care for lung sealing. PROGEL (Becton, Dickinson and Company, Franklin Lakes, New Jersey) hydrogel is the only lung sealant approved in the United States. However, due to its high stiffness, it can cause mismatches in compliance with the underlying lung tissue, and PROGEL has not yet been widely adopted. The secondary shear stress of the sealant-tissue joint ultimately leads to undesirable delamination. In addition, the low elongation at break of PROGEL results in the inability to apply the sealant in a fully contracted state. Therefore, PROGEL must be applied to the lung in a partially inflated state, which increases the complexity of the application process. PROGEL preparations will not set quickly, resulting in undesirable flow, ultimately resulting in poor coverage of the targeted lung surface and significant material waste. In addition, the poor visualization caused by the minimum contrast of the sealant on the lung surface may result in insufficient coverage.

[0003] In the Asia Pacific region, NEOVEIL (Gunze Limited, Tokyo, Japan), a bioresorbable polyglycolic acid (PGA) sheet used to reinforce sutures and staples, is used in combination with a fibrin sealant to seal lung tissue. However, NEOVEIL and fibrin sealants have lower bond strength than synthetic sealants. Lower bond strength and low elongation at break may result in undesirable delamination of the NEOVEIL mesh and fibrin sealant from the target tissue.

[0004] Lung sealants are used to prevent air leaks following lung surgery or injury. Lung sealants are particularly important for preventing complications such as persistent alveolar leak (PAL) and infection following lung surgery. However, sealing lung tissue is particularly challenging due to lung motion during breathing. A lung sealant with high tensile strength, high elongation at break, and low elastic modulus is needed that does not impede the natural circulatory motion of the lungs. Summary of the invention

[0005] The present invention addresses the limitations of currently existing biodegradable sealants. Provided herein are synthetic, biodegradable, two-component, rapid-setting liquid sealant compositions that form highly adherent and elastic hydrogels. The sealants provided herein have high tensile strength, high elongation at break, and low elastic modulus, and are particularly useful as lung sealants that do not impede the natural circulatory movement of the lungs.

[0006] Minimizing the stiffness of the lung sealants of the present invention provides unexpectedly advantageous lung sealing performance. Compared to sealants currently used for lung sealing, the lung sealants provided herein have reduced stiffness and greater elongation at break. The stiffness of the lung sealants provided herein has a stiffness of about 1 / 2.9 of that of PROGEL sealants and has an elongation at break that is about 7x higher than that of PROGEL sealants.

[0007] In one embodiment of the present invention, the sealant comprises a two-component, flowable, fast-setting liquid composition that forms a highly adherent and elastic biodegradable hydrogel.

[0008] In some embodiments, a method of preparing a lung sealant composition of the present disclosure comprises dissolving a first polyethylene glycol (PEG) polymer powder in an alkaline buffer to form a first component, and dissolving a second PEG polymer powder in a weakly acidic buffer to form a second component, wherein the two components are mixed immediately prior to or during application to a tissue or wound.

[0009] In some aspects, the method of preparing a lung sealant herein comprises: mixing an alkaline buffer with 4-arm PEG-NH2-HCl containing tocopherol to form a 4-arm PEG-NH2-HCl composition; separately mixing a weakly acidic buffer with 4-arm PEG-SG containing tocopherol to form a 4-arm PEG-SG composition; simultaneously delivering the 4-arm PEG-NH2-HCl and 4-arm PEG-SG compositions with an application device that allows the 4-arm PEG-NH2-HCl and 4-arm PEG-SG compositions to be fully mixed on the lung tissue; and allowing the lung sealant to cure on the lung tissue.

[0010] In a preferred embodiment, the lung sealant composition is composed of two high molecular weight (20 kDa) 4-arm PEG polymers, one PEG dissolved in an alkaline buffer and the other PEG dissolved in a weakly acidic buffer, for optimized preparation time and extended working time before solidification or gelation.

[0011] In some aspects, the biodegradable lung sealant comprises a first component comprising a first multi-arm PEG and an alkaline buffer for reconstitution of the first multi-arm PEG; and a second component comprising a second multi-arm PEG and a weakly acidic buffer for reconstitution of the second multi-arm PEG; wherein when the first component and the second component are combined, they produce an adherent and elastic biodegradable lung sealant.

[0012] In some embodiments, the flowable sealant of the present invention comprises a two-component composition, wherein the two components are mixed immediately before or during application to the tissue or wound, and wherein the first component comprises multi-arm PEG-amine (PEG-NH2) and the second component comprises multi-arm PEG-succinimidyl glutarate (PEG-SG). In some preferred embodiments, the first component of the sealant composition comprises 4-arm PEG-amine hydrochloride (4-arm PEG-NH2-HCl) 20 kDa, and the second component comprises 4-arm PEG-succinimidyl glutarate (4-arm PEG-SG) 20 kDa.

[0013] In a preferred embodiment, 4-Arm PEG-Amine 20 kDa is combined with a basic N-cyclohexyl-2-aminoethanesulfonic acid (CHES) buffer to form a first component of the sealant composition, and 4-Arm PEG-SG 20 kDa is combined with a weakly acidic citrate buffer to form a second component of the sealant composition.

[0014] In some embodiments, the first component and the second component are delivered to the lung tissue using a device that allows for intimate mixing of the components.

[0015] In some embodiments of the present disclosure, the PEG polymer includes a free radical scavenger for neutralizing reactive oxygen species (ROS). In some aspects, the free radical scavenger is a radiation protectant that improves the stability of the sealant composition to irradiation. In many aspects, the radiation protectant is an antioxidant (such as tocopherol). The example of suitable tocopherol is alpha-tocopherol, beta-tocopherol, gamma-tocopherol, delta-tocopherol, tocotrienol and a combination thereof. In a preferred embodiment, before the buffer is added to the PEG powder, the radiation protectant is compounded into the PEG powder.

[0016] In some embodiments, the sealant composition further comprises a colorant for improving visualization of the sealant against human tissue and enabling more consistent coverage of the targeted tissue. In some preferred embodiments, one or more colorants are compounded with the PEG powder. In some aspects of the invention, the colorant is FD&C Blue #1.

[0017] In some preferred embodiments, about 730 ppm to about 3000 ppm FD&C Blue #1 is added to the PEG-amine powder, the PEG-SG powder, or both the PEG-amine and the PEG-SG powder. More preferably, about 1000 ppm to about 1600 ppm FD&C Blue #1 is added to the PEG-amine powder, the PEG-SG powder, or both the PEG-amine and the PEG-SG powder.

[0018] In some aspects, the PEG powder used to prepare the components of the lung sealant of the present invention comprises both a first additive and a second additive, wherein the first additive is a radioprotectant (such as an antioxidant) and the second additive is a colorant. In one embodiment, the first additive is tocopherol and the second additive is FD&C blue #1.

[0019] In one aspect, the sealants and all components of the kits of the present disclosure, including PEG powder, buffers, solutions, and containers, are sterilized initially with at least a minimal X-ray irradiation dose, and most preferably up to about 39 kilograys (kGy) or up to about 47 kGy.

[0020] In another embodiment of the sealant, each of PEG-SG and / or PEG-amine is mixed with about 500 ppm to about 4000 ppm of tocopherol. In a preferred embodiment, about 1500 ppm to about 3000 ppm of tocopherol is added to each PEG.

[0021] In some embodiments, PEG-SG and PEG-amine each have an equal molecular weight. In a preferred embodiment, PEG-SG and PEG-amine each have a molecular weight of about 20 kDa.

[0022] In another embodiment, the final concentration of each of PEG-SG and PEG-amine in the sealant applied to the tissue is about 39 mg / mL to about 87 mg / mL, preferably about 52 mg / mL to about 77 mg / mL, and more preferably 67 mg / mL.

[0023] In some embodiments, at least a portion of each multi-arm PEG prior to dissolution exists in the form of particles having a size greater than or equal to about 250 microns. In another aspect, at least one multi-arm PEG has a particle size ranging from about 250 microns to about 1250 microns.

[0024] In another aspect, the PEG-amine has about 20% of the particles having a size of at least 710 μm to maximize the dissolution rate and minimize the sealant preparation time.

[0025] In another aspect, PEG-SG has about 40% of the particles having a size of at least 500 μm to maximize the dissolution rate and minimize the sealant preparation time.

[0026] In another embodiment, the pKa of the reconstitution buffer for the PEG-amine is preferably from about 8.0 pKa to about 9.7 pKa, and most preferably from about 8.8 pKa to about 9.4 pKa.

[0027] In another embodiment, the pH of the reconstitution buffer for the PEG-amine is at least 0.05 pH units above the buffer pKa.

[0028] In another aspect of the sealants provided herein, the preferred pH of the reconstituted PEG-amine / CHES solution is about 9.0 to about 10.5, and more preferably about 9.20 to about 9.80. In the most preferred embodiment, the PEG-amine / CHES solution has a pH of about 9.35 after reconstitution.

[0029] In another embodiment, the reconstitution buffer for the PEG-amine in the pre-filled device is about 190 mM to about 210 mM CHES buffer, the pH of which is preferably about 9.34 to about 9.80 prior to reconstitution.

[0030] In another aspect, the reconstitution buffer for the PEG-amine in the pre-filled device is about 180 mM to about 220 mM CHES buffer having a pH of about 9.35 to about 9.80 prior to reconstitution.

[0031] In another embodiment, the reconstitution buffer for the PEG-amine in the pre-filled device is about 180 mM to about 220 mM CHES buffer having a pH of about 9.37 to about 9.80 prior to reconstitution.

[0032] In a preferred embodiment, the reconstitution buffer for PEG-amine in the pre-filled device is 200 mM CHES buffer, which has a pH of 9.58 prior to reconstitution.

[0033] In another embodiment, the reconstitution buffer for PEG-SG is a citrate buffer having an initial pH of ≤7.0 and a concentration of about 3.5 mM to about 15 mM, and more preferably having a concentration of about 5.5 mM to about 12.5 mM.

[0034] In a preferred embodiment, prior to irradiation, the concentration of the citrate buffer is 9.04 mM and the initial pH is about 4.5.

[0035] In another embodiment, a colorant such as FD&C blue #1 is compounded into one or both dry PEG powders. In another aspect, FD&C blue #1 is compounded into one or both PEG powders at a concentration of about 730 ppm to about 3000 ppm prior to irradiation.

[0036] In another embodiment of the device, FD&C Blue #1 is increased to up to 300 ppm to account for color loss due to irradiation. Preferably, the final concentration of FD&C Blue #1 in the lung sealant of the present invention is from about 50 ug / mL to about 100 ug / mL.

[0037] In a preferred embodiment, the lung sealant comprises two 4-arm PEGs, wherein the first PEG is 4-arm PEG-NH2-HCl and the second PEG is 4-arm PEG-SG, the alkaline buffer is CHES, the weakly acidic buffer is citrate buffer, the antioxidant is tocopherol, and the colorant is FD&C Blue #1, and wherein the final concentration of the lung sealant composition after combining the components is 67 mg / mL 4-arm PEG-SG (20 kDa), 67 mg / mL 4-arm PEG-NH2-HCl (20 kDa), 100 mM CHES, 4.5 mM citrate buffer, 340 μg / mL tocopherol, and 88 ug / mL FD&C Blue #1.

[0038] In some embodiments of the present invention, kits are provided, wherein each kit comprises two dry PEG powders and two buffers. In a preferred embodiment, the kit comprises dry 4-arm PEG-amine and dry 4-arm PEG-SG, an alkaline buffer and a weakly acidic buffer.

[0039] In another embodiment, the biodegradable sealant is combined with a contrast agent for locating the seal site at a later time. In one aspect, the contrast agent is a non-ionic contrast agent for radiopaqueness, such as iohexol.

[0040] In another aspect, the biodegradable sealant is combined with a contrast agent to facilitate detection by magnetic resonance imaging.

[0041] In another embodiment, the contrast agent is a radioactive agent that allows the use of radiation detection methods to locate the sealing site.

[0042] In another embodiment, the biodegradable sealant composition can be combined with a therapeutic agent to provide local delivery of the therapeutic agent. For example, the therapeutic agent can be one or more chemotherapeutic agents used to treat cancer.

[0043] In another embodiment, a method of using a lung sealant comprises: adding tocopherol to a 4-arm PEG-amine to form a 4-arm PEG-amine and tocopherol mixture; irradiating the 4-arm PEG-amine and tocopherol mixture; adding a basic buffer to the 4-arm PEG-amine and tocopherol mixture to form a first component of the lung sealant; adding tocopherol to a 4-arm PEG-NHS ester to form a 4-arm PEG-NHS ester and tocopherol mixture; irradiating the 4-arm PEG-NHS ester and tocopherol mixture; adding a weakly acidic buffer to the 4-arm PEG-NHS ester and tocopherol mixture to form a second component of the lung sealant; and mixing the first component and the second component using an application device and simultaneously applying the first component and the second component to lung tissue to form a lung sealant, and allowing the sealant to cure on the tissue.

[0044] In some aspects, in the methods of using the lung sealants herein, the 4-arm PEG-amine and the 4-arm PEG-NHS ester are each in the form of a dry powder.

[0045] In another aspect, the 4-arm PEG-amine and tocopherol mixture and the 4-arm PEG-NHS ester and tocopherol mixture are each irradiated with up to about 40 kilograys (kGy) of X-rays.

[0046] As used herein, the terms "comprises", "comprising", "having" and their grammatical variations should be considered to specify the stated features, integers, steps or components, but do not exclude the addition of one or more further features, integers, steps, components or groups thereof. These terms encompass the terms "consisting of" and "consisting essentially of". Furthermore, as used herein, the indefinite articles "a" and "an" mean "at least one" or "one or more", unless the context clearly indicates otherwise.

[0047] These and other aspects and advantages of the present invention will become more apparent from the following description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a graph showing the effect of different molecular weights of PEG-SG and PEG-amine on the maximum load at break of the lung sealant.

[0049] Figure 2 is a graph showing the effect of different molecular weights of PEG-SG and PEG-amine on the tensile elongation at break of lung sealants.

[0050] Figure 3 is a contour plot showing the estimation of the average maximum load at varying PEG-SG to PEG-amine ratios (r) and total polymer content (PC).

[0051] Figure 4Graph showing the tensile maximum load evaluation of two PEG candidates of the present invention (Candidate #1: 62 mg / mL PEG-SG and 62 mg / mL PEG-amine, and Candidate #2: 67 mg / mL PEG-SG and 67 mg / mL PEG-amine), and a mock PROGEL formulation ("Mock PROGEL") prepared based on publicly available information about a commercially available PROGEL sealant (65 mg / mL PEG-succinimidyl succinate, 150 mg / mL human serum albumin, 50 mM carbonate (pH=9.0)). The tensile maximum load of the lung sealant of the present invention was 2.1 times that of Mock ProGel.

[0052] Figure 5 It is a graph showing the elongation at break of two PEG candidates of the present invention (Candidate #1: 62 mg / mL PEG-SG and 62 mg / mL PEG-amine, and Candidate #2: 67 mg / mL PEG-SG and 67 mg / mL PEG-amine), and Mock ProGel (65 mg / mL PEG-succinimidyl succinate, 150 mg / mL human serum albumin, 50 mM carbonate (pH = 9.0)). The elongation at break of the two PEG candidates of the present invention is 7.2 times that of Mock ProGel.

[0053] Figure 6 It is a graph showing the stiffness of two PEG candidates of the present invention (candidate #1: 62 mg / mL PEG-SG and 62 mg / mL PEG-amine, and candidate #2: 67 mg / mL PEG-SG and 67 mg / mL PEG-amine), and Mock ProGel (65 mg / mL PEG-succinimidyl succinate, 150 mg / mL human serum albumin, 50 mM carbonate (pH = 9.0)). The stiffness of the two PEG candidates of the present invention is 1 / 2.9 of that of Mock ProGel.

[0054] Figure 7 is a graph of the maximum shear modulus (Pa) of the lung sealant when PEG-SG and PEG-amine were increased in concentration from 40 mg / mL to 100 mg / mL in equal ratios.

[0055] Figure 8 is a graph showing the polymerization time of the lung sealant when PEG-SG and PEG-amine were increased in concentration from 40 mg / mL to 100 mg / mL in equal ratios.

[0056] Fig. 9is a graph showing the polymerization rate of lung sealant when PEG-SG and PEG-amine are increased in concentration from 40 mg / mL to 100 mg / mL in equal ratios.

[0057] Figures 10A-10D is a graph showing the evaluation of different concentrations of BHT to reduce the adverse effects of irradiation on 4-arm PEG-OH, with respect to Mn (number average molecular weight) ( Fig. 10A )、Mp(maximum peak molecular weight)( Fig. 10B )、Mw(weight average molecular weight)( Fig. 10C ) and polydispersity index (PDI) ( Fig. 10D ).

[0058] Figures 11A-11D is a graph showing the evaluation of different concentrations of tocopherol to reduce the adverse effects of irradiation on 4-arm PEG-OH, with respect to Mn (number average molecular weight) ( Fig.11A )、Mp(maximum peak molecular weight)( Fig. 11B )、Mw(weight average molecular weight)( Fig. 11C ) and polydispersity index (PDI) ( Fig.11D ).

[0059] Figures 12A-12D is a graph showing the evaluation of the effect of 2000 ppm (±)-α-tocopherol (tocopherol) on reducing irradiation on the lung sealant PEG, with respect to Mn (number average molecular weight) ( Fig. 12A )、Mp(maximum peak molecular weight)( Fig. 12B )、Mw(weight average molecular weight)( Fig. 12C ) and polydispersity index (PDI) ( Fig.12D ).

[0060] Fig.13 is a graph showing the dose-dependent effect of X-ray irradiation (kGy) on the functionality of PEG-SG and PEG-amine, wherein 2000 ppm tocopherol was added to each of PEG-SG and PEG-amine.

[0061] Fig.14 is a graph showing the effect of different X-ray irradiation (kGy) doses on the generation of aldehyde and formate by PEG-amine and PEG-SG.

[0062] Fig.15 is a graph showing the effect of different X-ray irradiation (kGy) doses on the generation of PEG esters from PEG-amine and PEG-SG.

[0063] Fig.16 is a graph showing the loss of antioxidant tocopherol of PEG-amine and PEG-SG at different X-ray irradiation (kGy) doses.

[0064] Fig.17is a graph showing the solubility of PEG-amine samples of different particle sizes at a controlled maximum.

[0065] Fig.18 is a graph showing the solubility of PEG-amine samples of different particle sizes with controlled minimum and maximum ranges.

[0066] Fig.19 is a graph showing the solubility of PEG-SG samples of different particle sizes at a controlled maximum.

[0067] Fig. 20 is a graph showing the solubility of PEG-SG samples of different particle sizes with controlled minimum and maximum ranges.

[0068] Fig.21 is a graph showing the effect of buffer pKa on the polymerization time of PEG-SG and PEG-amine.

[0069] Fig. 22 is a graph showing the effect of different CHES pH on the polymerization rate of PEG-amine (HCl salt).

[0070] Fig.23 is a contour plot of the polymerization rate response at different pH and CHES concentrations.

[0071] Fig.24 is a graph showing the results of burst pressure testing performed at different angles to demonstrate how the improved stay-in-place ability of the lung sealant of the present invention affects performance compared to MockProGel.

[0072] Fig.25 is an interaction diagram showing that citrate buffer reduces PEG-SG hydrolysis. DETAILED DESCRIPTION

[0073] The biodegradable lung sealant of the present invention is applied as a liquid that is fast-setting to remain in the target tissue location and provide an adequate seal. The sealant has improved elasticity, tensile strength, visualization, and working time.

[0074] In addition, the sealants of the present invention surprisingly and unexpectedly have a shear modulus, polymerization time, and polymerization rate that are advantageous for sealing lung tissue. In one aspect, the lung sealants provided herein comprise a combination of an equimolecular weight polyethylene glycol (PEG) polymer and an optimal buffer system. PEG with a molecular weight of about 15 kDa to about 50 kDa is preferably used in the lung sealants of the present invention.

[0075] The polymerization kinetics of the lung sealants provided herein can be determined as follows:

[0076] (a) Maximum shear modulus, a measure of the sealant stiffness;

[0077] (b) polymerization time (k), defined as the time required to obtain 50% of the final mechanical properties of the sealant; and

[0078] (c) The polymerization rate defined as the maximum slope of the shear modulus.

[0079] The polymerization time (k) analyzes the shear modulus normalized to the maximum shear modulus over time. The polymerization time provides insight into the cure time (the time required to achieve final mechanical properties), but also allows for an indirect determination of the setting time, i.e., the time required for the sealant to stop flowing. The setting time cannot be directly quantified as the sealant setting in seconds.

[0080] The polymerization rate provides a measure of the rate at which the shear modulus of the sealant increases over time. The polymerization rate is sensitive to both the polymerization time and the final hydrogel mechanical properties.

[0081] The effectiveness of a sealant, or the ability of a sealant to provide a strong seal, is determined by the mechanical properties of the sealant. Sealant mechanical properties are measured via set tensile testing and shear modulus.

[0082] The PEG suitable for the lung sealant of the present invention is a multi-arm PEG, such as 2, 3, 4, 6 or 8 multi-arm PEG. In some preferred embodiments, PEG is a 4-arm PEG. In some aspects, the multi-arm PEG is a multi-arm PEG derivative. In some embodiments, the multi-arm PEG derivative is a multi-arm PEG-amine hydrochloric acid (HCl) salt. For example, multi-arm PEG is commercially available from JenKemTechnology (Plano, Texas) or NOF Corporation (Tokyo, Japan). In some embodiments, the molecular weight of the multi-arm PEG is about 15kDa to about 50kDa, and most preferably about 20kDa. In some embodiments, the lung sealant provided herein comprises a multi-arm PEG having a reactive functional group at each end of the arm, such as an N-hydroxysuccinimide (NHS) ester group capable of forming a stable conjugate, i.e., an amide bond with a PEG-amine. Exemplary of suitable PEGs for use in the sealants provided herein are 4-arm PEG-succinimidyl glutarate (SG), 4-arm PEG-succinimidyl valerate, 4-arm PEG-succinimidyl carbonate, 4-arm PEG-succinimidyl succinate, 4-arm PEG-succinimidyl butyrate, 4-arm PEG-succinimidyl succinamide, 4-arm PEG-succinimidyl propionate, 4-arm PEG-sulfosuccinimidyl glutarate, 4-arm PEG-sulfosuccinimidyl valerate, 4-arm PEG-sulfosuccinimidyl carbonate, 4-arm PEG-succinimidyl carboxymethyl ester, 4-arm PEG-sulfosuccinimidyl succinate, 4-arm PEG-sulfosuccinimidyl butyrate, 4-arm PEG-sulfosuccinimidyl succinamide, 4-arm PEG-sulfosuccinimidyl propionate, 4-arm PEG-amine, 4-arm PEG-isocyanate, 4-arm PEG-imidate, and 4-arm PEG-maleimide.

[0083] In another aspect, the sealants provided herein can include a thiol reacted with PEG-NHS ester and PEG-maleimide.

[0084] In some embodiments, the lung sealant comprises PEG, the total final concentration of which in the sealant is about 39 mg / mL to about 87 mg / mL. In a preferred embodiment, the total concentration of each PEG is about 67 mg / mL. Examples of preferred PEGs are 4-arm PEG-succinimidyl glutarate, molecular weight 20 kDa (4-arm-PEG-SG-20k) (67 mg / mL), available from JenKem Technology or NOF Corporation, and 4-arm PEG-amine, molecular weight 20 kDa (4-arm-PEG-NH2-20k) (67 mg / mL), available from JenKem Technology or NOF Corporation. In one aspect, the final concentrations of PEG-SG and PEG-amine in the sealant applied to the tissue are each about 39 mg / mL to about 87 mg / mL, preferably about 52 mg / mL to about 77 mg / mL, and more preferably about 67 mg / mL.

[0085] The particle size distribution of off-the-shelf PEG that gives maximum dissolution using the methods provided herein is used to prepare the biodegradable lung sealant of the present invention. However, particle size has a significant effect on the dissolution rate of PEG. Unexpectedly, larger particle sizes lead to faster dissolution by reducing the tendency of PEG to aggregate and adhere to the walls of the glass vial.

[0086] For PEG-amine, a maximum particle size of at least 710 μm is preferred. For PEG-SG (when it is dissolved in a lower concentration buffer), a maximum particle size of at least 500 μm is most preferred. Lower maximum particle sizes will dissolve but require longer preparation times.

[0087] On the other hand, suitable buffers for preparing the lung sealants of the present invention are alkaline buffers, such as N-cyclohexyl-2-aminoethanesulfonic acid (CHES) buffer, 2-amino-2-methyl-1,3-propanediol, N-tris(hydroxymethyl)methyl-4-aminobutanesulfonic acid, N-(1,1-dimethyl-2-hydroxyethyl)-3-amino-2-hydroxypropanesulfonic acid, 3-(cyclohexylamino)-2-hydroxy-1-propanesulfonic acid, pyridoxine buffer and weak acidic buffers (such as citrate buffer). Preferably, the pH of the weak acidic buffer is from about 4 to about 6 or up to 7.

[0088] Carbonate buffers are not preferred due to increased fluidity resulting from insufficient buffering capacity at pH 9. Although higher pH can reduce fluidity, undesirable hydrolysis and tissue reactions may occur.

[0089] Higher molecular weight PEGs result in lung sealants with higher tensile elongation at break. However, larger molecular weight PEGs may exhibit reduced renal clearance and an undesirably longer half-life. In a preferred embodiment, a 20 kDa molecular weight PEG provides a desired balance between hydrogel mechanical properties and excretion / clearance time. In one aspect, the molecular weights of the two PEGs are similar or equal. In a preferred aspect, the PEGs are PEG-SG and PEG-amine, each having a molecular weight of 20 kDa.

[0090] The lung sealants provided herein have lower stiffness relative to currently commercially available lung sealants. Surprisingly and unexpectedly, the lung sealants herein exhibit greater strength, elasticity, and compliance than currently commercially available products. For example, the elongation at break of the lung sealants of the present invention is about 7 times that of the Mock ProGel formulation ( Figure 5 ), and the stiffness is about 1 / 2.9 lower than that of the Mock ProGel preparation ( Figure 6 ).

[0091] In some aspects, radioprotectants (such as tocopherol) reduce changes in PEG molecular weight (MW). Irradiation of PEG is preferably performed in a hypoxic environment.

[0092] The PEG-amine is preferably in protonated form to prevent degradation of functionality caused by high irradiation.

[0093] In some embodiments of the invention, the lung sealant comprises a colorant. In some aspects, the colorant is contained in one or both of the dry PEG powders. In another aspect, the colorant is compounded into the dry PEG-SG powder. Examples of colorants for use in the lung sealants of the invention are FD&C Blue #1, FD&C Blue #2, FD&C Green #3, FD&C Yellow #6, and combinations thereof. In a preferred embodiment, about 1000 ppm to about 1600 ppm of the colorant FD&C Blue #1 is compounded into the dry PEG-SG powder. Preferably, the final concentration of FD&C Blue #1 in the lung sealant of the invention is about 50 ug / mL to about 100 ug / mL.

[0094] In one embodiment, a kit comprising two dry PEG powders and two buffers is provided. In a preferred embodiment, the kit comprises dry 4-arm PEG-amine powder and dry 4-arm PEG-SG powder, CHES buffer and citrate buffer.

[0095] The pH of the PEG-amine solution after dissolution is preferably from about 9.0 to about 10.5, more preferably from about 9.20 to about 9.80, and most preferably about pH 9.35.

[0096] The lung sealants of the present invention can be used to prevent persistent pulmonary air leak (PAL) following lung volume reduction (LVR), biological lung volume reduction (Bio-LVR), lung volume reduction surgery (e.g., lung volume reduction resection for the treatment of emphysema), bleb resection, thoracotomy, sternotomy, and thoracic surgery.

[0097] Additional details regarding the lung sealants of the present invention are provided in the following non-limiting examples.

[0098] Example

[0099] Example 1

[0100] Effect of molecular weight of PEG polymer on the mechanical properties of hydrogels.

[0101] To test tensile strength, elongation at break, and elastic modulus, a study was conducted to understand the effect of the molecular weight of PEG-amine and PEG-SG on the mechanical properties of the hydrogels at a constant molar concentration of each PEG. The PEG-amine molecular weight was varied from 5 kDa to 20 kDa, and the PEG-SG molecular weight was varied from 10 kDa to 20 kDa. A 50 mM carbonate buffer system was used for all cases.

[0102] like Figure 1 As shown in the graph in , the maximum load at break of the tested sealant formulations increased with increasing molecular weight of each PEG, and the maximum load increased the most when the molecular weights of the two PEGs were the same.

[0103] Interestingly, if Figure 2 As shown, the tensile elongation at break also increases with the increase of the molecular weight of each PEG. However, PEG with a molecular weight greater than about 50 kDa exhibits reduced renal clearance. When the molecular weight of each PEG is 20 kDa, it is found that a preferred balance occurs between the hydrogel mechanical properties and the clearance time.

[0104] Example 2

[0105] Effect of PEG concentration on shear modulus, polymerization time and polymerization rate

[0106] A study was conducted to characterize the concentration range of PEG-SG (20 kDa) and PEG-amine (20 kDa) with a 100 mM CHES (pH = 9.35), 3.75 mM citrate (pH = 5.0) buffer system. PEG-SG and PEG-amine were tested by increasing the concentration from 40 mg / mL to 100 mg / mL in equal ratios.

[0107] The polymerization kinetics of the sealant were tested by oscillatory rheological time sweeps for 300 seconds at 1 Hz, 150 Pa. The shear modulus over time was fit to the Hill Equation to provide three outputs:

[0108] (1) Maximum shear modulus, a measure of the stiffness of the formulation;

[0109] (2) polymerization time (k), defined as the time to achieve 50% of the final mechanical properties; and

[0110] (3) Polymerization rate, defined as the maximum slope of the shear modulus.

[0111] To analyze the linear effect of this bulk polymerization system, the study was designed using the total polymer content and the ratio of the two reagents as factors in a central composite design.

[0112] Total polymer content (PC) = [PEG-SG] + [PEG-amine]

[0113]

[0114] In this study, Figure 3 As shown, a linear increase in the tensile maximum (max) load was observed with increasing polymer content, and a quadratic effect of r was observed, with a maximum near r = 1.0, or the same concentration of PEG-SG and PEG-amine.

[0115] like Figure 4 As shown, the stiffness of the sealant of the present invention is very low relative to the simulated formulation of the current commercial sealant. In the tensile evaluation, two candidate sealants of the present invention were tested compared to Mock ProGel (65 mg / mL PEG-succinimidyl succinate, 150 mg / mL human serum albumin, 50 mM carbonate (pH = 9.0)). It was observed that the tensile maximum load of the two candidate sealants of the present invention was 2.1 times that of Mock ProGel. The intervals were calculated using individual standard deviations.

[0116] A theoretical analysis of the ultimate tensile stress requirements of the sealant for a human lung was performed. The lung was assumed to be a spherical balloon with a volume of 5371 mL with an extreme worst case (male, right lung, 99.99 percentile), and the sealant thickness was assumed to be 1 mm. The theoretical calculation of the burst pressure is as follows:

[0117]

[0118] Where UTS is the ultimate tensile stress of the sealant, δ is the thickness of the sealant, and R is the radius of the lung. A safety factor of 3 was applied to a standard intrathoracic pressure of 30 cm HO, setting the burst pressure to 90 cm HO. The required ultimate tensile strength was calculated to be 47.8 kPa, which corresponds to a PEG concentration of 39.5 mg / mL PEG-SG and 39.5 mg / mL PEG-amine.

[0119] Different concentrations of PEG-SG and PEG-amine were tested. The concentrations of PEG-SG and PEG-amine were each increased from 40 mg / mL to 100 mg / mL in equal ratios. Figure 7 As shown, PEG concentration has a significant effect on shear modulus (p < 0.01). Interestingly, the peak of the maximum shear modulus was observed between 67mg / mL-77mg / mL, which was not significantly different from 52mg / mL-62mg / mL. The shear modulus dropped sharply below 52mg / mL and above 77mg / mL.

[0120] like Figure 8 As shown, it was observed that polymerization times of less than 25 seconds were associated with acceptable polymerization mechanical properties. According to the regression model, the lower limit determined by the mechanical requirement of 39.5 mg / mL had a calculated polymerization time of 21 seconds. The upper limit of 86.5 mg / mL corresponded to a polymerization time of 25 seconds.

[0121] The PEG concentration had a significant effect on the polymerization rate (p<0.01). Fig. 9 As shown, the polymerization rate showed a significant peak at 67 mg / mL and ranged from about 52 mg / mL to about 77 mg / mL, indicating that there was no significant difference in the rapid polymerization rate.

[0122] Integrating data from mechanical analysis and polymerization time assessments, the final concentration of each PEG in the lung sealants of the present invention is about 39 mg / mL to about 87 mg / mL, preferably about 52 mg / mL to about 77 mg / mL, and more preferably 67 mg / mL. In some aspects, the concentration of PEG in the lung sealants of the present invention is about 39 mg / mL to about 87 mg / mL, more preferably about 52 mg / mL to about 77 mg / mL, and most preferably about 67 mg / mL.

[0123] Example 3

[0124] PEG irradiation

[0125] Gamma and X-ray irradiation studies were performed to evaluate the ability of the lung sealant PEG to be sterilized. PEG irradiation was performed under a nitrogen purge.

[0126] PEG was dosed alone under ambient conditions in glass vials and gamma irradiated to 27.9 kGy-29.5 kGy. When combined with non-irradiated PEG-amine, PEG-SG degraded significantly and did not form a hydrogel. PEG-amine lost 30% of its functionality and exhibited significant cross-linking of the PEG backbone.

[0127] Subsequent studies were performed in the same manner, but the vials were evacuated to 100 mTorr and purged with nitrogen to 600 Torr, and the PEG-amine was irradiated in the protonated hydrochloride form. Relative to ambient conditions, PEG-SG had 4% less functional degradation, an order of magnitude less low molecular weight degradants, and efficient crosslinking occurred when mixed with PEG-amine. PEG-amine had 18% less functional degradation, and chain degradation was also reduced.

[0128] These results suggest that irradiation of lung sealant PEG must be done under hypoxic conditions and that the PEG-amine should be in a protonated form to prevent a significant reduction in functionality.

[0129] To reduce the adverse effects of the irradiation process on the lung sealant PEG, two antioxidants, BHT and tocopherol, were added at different concentrations up to 4000 ppm.

[0130] like Figures 10A-10D As shown, BHT was added at different concentrations to test the adverse effects of irradiation on 4-arm PEG-OH. Fig. 10A )、Mp(maximum peak molecular weight)( Fig. 10B )、Mw(weight average molecular weight) Fig. 10C ) and polydispersity index (PDI) ( Fig. 10D ).

[0131] There is no significant effect on molecular weight distribution and no correlation with viscosity changes with BHT concentration. Residual BHT is already present in PEG as an oxidation protectant at concentrations of 300 ppm or less. Adding additional BHT does not reduce the effect of the irradiation process on 4-arm PEG-OH.

[0132] like Figures 11A-11D Tocopherol was added at different concentrations to test the adverse effects of irradiation on 4-arm PEG-OH, as shown in Fig.11A )、Mp(maximum peak molecular weight)( Fig. 11B )、Mw(weight average molecular weight)( Fig. 11C ) and polydispersity index (PDI) ( Fig.11D ).

[0133] The addition of tocopherol showed a linear decrease in molecular weight distribution after irradiation as the tocopherol concentration increased to 1500 ppm and the viscosity decreased to 2000 ppm.

[0134] Therefore, a range of 1500ppm-4000ppm tocopherol added to the multi-arm PEG is most effective in achieving the following beneficial effects:

[0135] 1) Reduce the loss of mechanical properties under uniaxial tension, including ultimate tensile strength and elongation at break;

[0136] 2) increase the maximum acceptable dose of X-ray radiation; and

[0137] 3) To reduce the viscosity of the resulting PEG solution to reduce expressivity and improve the ease of spraying or dripping the lung sealant composition onto lung tissue.

[0138] To further understand the effect of tocopherol on lung sealant PEG during irradiation, the dose-dependent effect of X-ray irradiation with 2000 ppm (±)-α-tocopherol (tocopherol) was studied. PEG was analyzed for changes in molecular weight distribution (as measured by gel permeation chromatography (GPC)), chemical functionality (by NMR), polymerization time, and coagulation tensile testing.

[0139] like Figures 12A-12D As shown, Mn (number average molecular weight) ( Fig. 12A ) and Mp (molecular weight of the highest peak) ( Fig. 12B ) changes were relatively small. For PEG-SG and PEG-amine, Mn had a maximum change of 6% and 13%, respectively. For PEG-SG and PEG-amine, Mp showed a maximum change of 13% and 4%, respectively. Mw (weight average molecular weight) ( Fig. 12C ) showed more significant changes of up to 18% and 34% for PEG-SG and PEG-amine, respectively. However, for each PEG, the change was less than 10% up to 25 kGy and 17% at 35 kGy, indicating that the greatest differences were observed above 35 kGy. Driven by the decrease in Mn and the increase in Mw, the polydispersity index (PDI) of PEG-amine ( Fig.12D ) to a greater extent than PEG-SG.

[0140] The dose-dependent effect of X-ray irradiation (kGy) on the functionalities of PEG-SG and PEG-amine is shown in Figure 2. Fig.13As shown, 2000ppm tocopherol was added to each of PEG-SG and PEG-amine. PEG was X-ray irradiated at 37.6 kilograys (kGy) to 46.8kGy. X-ray irradiation had a significant dose-dependent effect on PEG-SG functionality (p<0.01, one-way ANOVA), but had no significant effect on PEG-amine functionality (p=0.11, one-way ANOVA). According to linear regression, for PEG-SG, for every 1kGy increase in irradiation, the functionality was lost by 0.14%. For PEG-SG, a maximum loss of 10% was observed at 46kGy.

[0141] Low molecular weight PEG oxidation products were observed in the irradiated samples, but no significant differences were observed (one-way ANOVA). PEG aldehyde and formate remained below 0.05% in PEG-amine samples up to 37 kGy and in PEG-SG samples at all irradiation doses. Fig.14 As shown, at 46 kGy, 0.01% aldehyde and formate was observed in the PEG-SG sample, and at 46 kGy, 0.01%-0.22% aldehyde and formate was observed in the PEG-amine samples, yielding a mean of approximately 0.11% for PEG-amine, indicating that for PEG-amine, the response to irradiation can vary more at this dose.

[0142] like Fig.15 As shown, PEG esters remained below 0.15% on average in PEG-SG at all irradiation doses and in PEG-amine up to 37 kGy. At 46 kGy, 0.21% of PEG esters were observed in PEG-amine and 0.12% of PEG esters were observed in PEG-SG, indicating that for PEG-amines, the response to irradiation may vary more at this dose.

[0143] The concentration of tocopherol was quantified by HPLC. Fig.16 As shown, PEG-amine exhibited a linear decrease in tocopherol as the irradiation dose increased to 37 kGy. At higher doses, the tocopherol concentration decreased to approximately 6% of the tocopherol concentration in the control sample. PEG-SG exhibited a more significant decrease in tocopherol, retaining approximately 8% at 37 kGy.

[0144] Tocopherol concentration was significantly affected by irradiation dose in PEG-amine (p<0.01) and PEG-SG (p<0.01, one-way ANOVA). Given that the response was linear up to 37 kGy, regression was performed to understand the change in tocopherol concentration due to X-ray irradiation. For PEG-amine and PEG-SG, 6.4 ppm and 47 ppm tocopherol were lost for each 1 kGy increase in X-ray irradiation, respectively.

[0145] Regarding the coagulation mechanical properties, no significant differences were observed in the percent elongation up to 45 kGy and the tensile strength and modulus up to 35 kGy.

[0146] When evaluated in the rheological polymerization assessment, the irradiation dose had a significant effect on the polymerization time and polymerization rate. However, with the exception of 37 kGy, which had a polymerization time 64.2% longer than the control, there were no significant differences between the groups for all irradiation doses tested.

[0147] The use of about 1500 ppm to about 3000 ppm of tocopherol in the lung sealant PEG compositions provided herein is most preferred because this range minimizes the amount of tocopherol required while obtaining the full beneficial effects of tocopherol as a radioprotectant. However, tocopherol concentrations of about 500 ppm to about 4000 ppm also have a significant beneficial effect on the PEG molecular weight distribution. The maximum X-ray irradiation dose is most preferably about 35 kGy to about 45 kGy.

[0148] Example 4

[0149] PEG particle size distribution

[0150] The lung sealant provided herein is prepared from PEG powder and buffer. The time required to dissolve the PEG powder is tested to identify the desired particle size range. PEG (JenKem) is sieved into different particle size ranges, dried under vacuum and loaded into the lung sealant application device. PEG is dissolved in the application device by the syringe method: 3 strokes (each stroke represents a cycle of pushing and pulling the syringe plunger in the device), followed by eddy current treatment with a constant circular vortex for 1 minute. Dissolution is tested spectrophotometrically at 534nm with barium chloride and potassium iodide.

[0151] Two groups of PEG-amine samples were tested: 1) with a controlled maximum particle size ( Fig.17 ), and 2) a particle size with a controlled minimum and maximum range ( Fig.18 ). Surprisingly, Fig.17 As shown in Figure 1, there is a statistically significant increase in solubility as the maximum particle size increases up to 710 μm, after which there is no further increase in solubility. Relative to the maximum particle size group of 1200 μm, the solubility of the particle size groups of 125 μm, 250 μm, 500 μm, and 710 μm is 36%, 51%, 83%, and 97%, respectively. Small particles clump and aggregate and slow dissolution. Similar trends are observed when comparing particle size to the controlled minimum and maximum ranges. Fig.18As shown in the graph in , there is a statistically significant increase in solubility, with the 710 μm-1200 μm range showing the greatest and most preferred dissolution. Relative to the largest particle size group of 710 μm-1200 μm, the solubility of the particle size groups of 125 μm-250 μm range, 250 μm-500 μm range, and 500 μm-710 μm range are 67%, 86%, and 87%, respectively.

[0152] Two groups of PEG-SG samples were tested: 1) with a controlled maximum particle size ( Fig.19 ), and 2) a particle size with a controlled minimum and maximum range ( Fig. 20 ). In the lung sealant formulation of the present invention, PEG-SG can be more easily dissolved because the citrate buffer concentration is lower, thereby allowing PEG-SG to dissolve more easily. Similar to PEG-amine, particle size has a significant effect on the degree of solubility. However, as Fig.19 As shown in the graph in , for PEG-SG, PEG-SG with a maximum particle size of 500 μm, 710 μm, and 1200 μm completely dissolved and dissolved significantly more than PEG-SG with a lower maximum particle size (125 μm and 250 μm). Particle sizes greater than 1200 μm were also tested and also completely dissolved. Fig. 20 As shown in the graph in , when comparing the particle size range, there is a statistically significant increase in solubility up to the particle size of 500-710 μm, after which all groups are completely dissolved. The solubility of the 125 μm-250 μm range and the 250 μm-500 μm range relative to the 500 μm-710 μm range is 40% and 86%, respectively. The lower particle size range of PEG-SG results in similar phenomena observed as PEG-amine. However, when a particle size of 500 μm is present, PEG-SG is completely dissolved.

[0153] Particle size has a significant effect on the dissolution rate of PEG. Unexpectedly, larger particle sizes lead to faster dissolution by reducing the tendency of PEG to aggregate and adhere to the walls of the glass vial. For PEG-amine, in a particle size distribution, it is most preferred that particles with a particle size of up to 710 μm or more, or up to 1200 μm, are present in the distribution, along with smaller particles.

[0154] For PEG-SG (because it dissolves in lower concentrations of buffer), it is most preferred that there be particles up to 500 μm or larger, or up to 1200 microns, in the particle size distribution, along with smaller particles. A lower maximum particle size will still eventually dissolve, but will require longer preparation times.

[0155] Example 5

[0156] PEG-amine buffer (alkaline buffer)

[0157] NHS ester / amine chemistry is typically performed at pH 7.2 to pH 8.5 to produce a stable amide bond. The most common buffers utilized are phosphate buffer, carbonate-bicarbonate buffer, HEPES buffer, or borate buffer. The pH must be maintained at a slightly alkaline pH in order to maintain a sufficient proportion of the amine in the deprotonated state. However, as the pH increases, the hydrolysis rate of the PEG-SG ester also increases. Therefore, when developing a fast-setting sealant based on this chemistry, the balance between increasing the reaction rate and the loss of reactivity of the PEG-SG must be considered.

[0158] Unexpectedly, a common buffer used for this chemistry, carbonate buffer, was found to be inadequate for use in the methods of making the lung sealants of the present invention. A 100 mM carbonate buffer system was tested in a 28.5 mg / mL 4-arm PEG-amine-10k, 75 mg / mL 4-arm PEG-SG-20k system at different pHs using a 40 degree ramp travel distance assessment. It was found that the travel distance decreased significantly as the pH increased. At pH 9.0, the travel distance was 236 mm, at pH 10.0, the travel distance was 140 mm, and at pH 11.0, the travel distance was 85 mm. In comparison, the fibrin sealant traveled approximately 60 mm in the same assessment. Considering that a pH greater than 10.5 is considered corrosive, it was found that a carbonate buffer system was insufficient to maintain a high enough pH to obtain satisfactory polymerization kinetics due to unacceptable fluidity at pH 9.

[0159] Other candidate buffers were investigated with the goal of minimizing the initial pH required for the sealant to avoid any possible corrosive effects. Several candidate buffers were tested for their ability to maintain the pH of the sealant at 9.0 ± 0.5 pH throughout the cross-linking reaction. A methoxy PEG-SG alternative material was used in place of the 4-arm PEG-SG to avoid gelation and allow for continuous measurement of the pH of the reaction when combined with PEG-amine.

[0160] At 100 mM (final concentration), the pH was measured over the course of 10 minutes to determine how well the buffer maintained the pH when started at pH 9. The data indicated that borate buffer, CHES buffer, and pyridoxine buffer were acceptable, having a pKa range of 9-9.4.

[0161] As shown in Table 1 below, a range of buffer pKas from 7.2 pKa to 10.3 pKa were investigated to understand the appropriate range for NHS ester / amine chemistry. The pH of all buffers after reconstitution was kept constant at pH = 9.35. A final PEG-SG and PEG-amine concentration of 67 mg / mL was tested.

[0162] Table 1

[0163] Buffer pKa Phosphate 7.21 TAPSO 7.6 TAPS 8.4 AMPD 8.8 TABS 8.9 CHES 9.3 Pyridoxine 9.4 CAPSO 9.6 Carbonate 10.3

[0164] like Fig.21 As shown, polymerization time is significantly affected by the pKa of the buffer (p<0.01). At pH 9.35, buffers with a pKa range of 8.8 to 9.4 exhibit significantly reduced polymerization times than those buffers with pKa ranges outside this range. Buffer pKas of 8.4 and 9.6 also exhibit fast polymerization rates. Quadratic regression was used to determine the range of pKas that yielded acceptable polymerization times. For polymerization times of less than 25 seconds, the preferred pKa buffer range is from about 7.9 to about 9.7.

[0165] This discovery of a buffer for use in preparing the lung sealants of the present invention is unexpected and contradicts the use of buffers commonly used in sealant formulations. Most commercially available sealant products utilizing NHS ester / amine chemistry utilize phosphates, triethanolamine, carbonates, or a combination of such buffer systems in their formulations. The rationale for using such buffers is generally rarely discussed, although the choice may be due to the widespread use of these buffers across the medical device and pharmaceutical formulation fields, as well as the proven safety data. The lung sealant compositions of the present invention provided herein include biological buffers having a narrower pKa range, preferably from about 7.9 to about 9.7, and most preferably from about 8.8 to about 9.4.

[0166] In addition, in order to select the correct candidate buffer, the pH after reconstruction is considered to optimize the setting time of the sealant. In this evaluation, the polymerization time of the sealant is evaluated by evaluating the travel distance on a 40-degree slope. It was found that when the pH of the buffer system was increased to just above the pKa of the system, a significant reduction in the travel distance was observed. This observation was also consistent in borate buffer (pKa = 9.0) and pyridoxine buffer (pKa = 9.4). These results indicate that the setting time of the sealant can be significantly reduced by increasing the pH after reconstruction to at least 0.05 pH units above the pKa of the buffer.

[0167] In a two-part experiment, CHES buffer (pKa=9.3) was tested in the polymerization time rheology method. In the first part of the study, a wide range of pH from 8.0 to 10.5 was tested. It was observed that the sealant did not polymerize at pH ≤ 8.5. In addition, the maximum shear modulus decreased linearly as the pH increased from 9.0 to 10.5. The polymerization time decreased significantly from 9.0 to 9.5 and did not decrease further. Since pH has a significant effect on the polymerization rate, the fastest polymerization rate was observed at pH=9.5.

[0168] In the second part of the experiment, a higher resolution study was performed to evaluate pH 9.05 to 9.8 in increments of 0.15 units. In this study, a decrease in the maximum shear modulus of approximately 3% was observed for each 0.15 pH unit increase. However, there was a significant decrease in polymerization time from 9.05 to 9.35, after which no significant differences were observed. Fig. 22 As shown, the polymerization rate exhibited a maximum average value at 9.35, but had no significant difference from 9.20 to 9.80.

[0169] Therefore, the pH of CHES after dissolution of the PEG-amine is preferably from about 9.0 to about 10.5, more preferably from about 9.20 to about 9.80, and most preferably pH 9.35. Fig.23 As shown, there is a significant effect on the polymerization rate due to both CHES concentration (p<0.01) and pH (p<0.01). There is a significant quadratic effect of pH (p<0.01). The fastest polymerization rates were observed at high CHES concentrations and moderate pH. As pH increased beyond approximately 9.55, the polymerization rate decreased.

[0170] Example 6

[0171] Adhesion evaluation

[0172] The lung sealant of the present invention was compared to Mock ProGel for its ability to stay in place. In this evaluation, 4 mL of sealant was manually sprayed onto a 2 cm wide target area at an approximate rate of 2 mL / s on a 40 degree ramp. The percentage of sealant remaining in the target area was measured gravimetrically.

[0173] The prototype lung sealant formulation of the present invention was compared to the Mock ProGel formulation. The lung sealant formulation tested was 78 mg / mL 4-arm PEG-AmineHCl-20k, 63 mg / mL 4-arm PEG-SG-20k, 100 mM CHES (pH=9.35). The MockProGel formulation was 65 mg / mL linear PEG-SS-4k, 150 mg / mL bovine serum albumin, 50 mM carbonate buffer (pH=9.0).

[0174] Next, a functional burst pressure test was performed to understand how the improved ability to stay in place would affect performance. In this evaluation, the formulations tested in the slope adhesion evaluation were tested here. Fig.24As shown, burst pressure testing was performed on 0° (flat), 30°, and 45° bevels on porcine pleural tissue with a 1 mm circular notch. The sealant was sprayed onto the tissue, cured for 10 minutes, and the tissue was pressurized until burst.

[0175] Qualitatively, the lung sealants of the invention were observed to completely cover the target tissue at all angles tested. MockProGel completely covered the tissue at 0° bevel, but exposed some tissue at 30°, and at 45°, most of the sealant flowed off the bevel, forming a hydrogel as it flowed.

[0176] Quantitatively, the burst pressure of the lung sealant of the present invention did not change significantly with the bevel angle. On the other hand, the Mock ProGel decreased significantly with increasing bevel angle, decreasing by 77% at 45° relative to the flat condition.

[0177] Example 7

[0178] PEG-SG buffer (weakly acidic buffer)

[0179] NHS activated esters such as PEG-SG are known to hydrolyze over time. Therefore, PEG-SG must be kept in dry powder form until the time of use. The rate of hydrolysis depends on the solution pH, with the half-life decreasing as pH increases. The rate of hydrolysis must be considered because it determines the working time, which is defined as the time from dissolution of the PEG to application of the sealant.

[0180] As shown in Table 3 below, currently available products with NHS ester chemistries have relatively short working times. ProGel, DuraSeal, Adherus, and CoSeal include working times of 20 minutes, 60 minutes, 60 minutes, and 120 minutes, respectively, in their instructions for use. ProGel does not use a buffered aqueous solution to dissolve the PEG ester in the sealant formulation. DuraSeal and Adherus use a phosphate buffer system to extend the working time to 60 minutes, while CoSeal uses a phosphate buffer system to extend the working time to 120 minutes.

[0181] Table 3

[0182] Buffer system pH Working hours ProGel none Uncontrolled 20 DuraSeal 3.25 mM phosphate 4.0 60 Adherus Phosphate 6.0 60 CoSeal 0.5 mM phosphate 6.0 120

[0183] *These values ​​are based on publicly available information.

[0184] The method for preparing the lung sealant provided herein utilizes a weakly acidic buffer to keep PEG-SG at a weakly acidic pH. The degree of hydrolysis of PEG-SG over time is monitored using spectrophotometry. Briefly, PEG-SG is dissolved in the buffer of interest, 10 μl of sample is added to the microplate, and incubated for a set period of time. At each time point, 100 μl of 10X PBS (pH=7.8) is added to the solution to stop further hydrolysis, and the absorbance at 260 nm is immediately measured.

[0185] like Fig.25 As shown, citrate buffers at pH 3.0, 4.0, 5.0, 6.0 and 7.0 were compared to water (assuming pH = 7.0) by three-way ANOVA. Citrate buffer was found to significantly reduce the extent of hydrolysis of PEG-SG by 2.5% relative to water over the course of two hours.

[0186] The data support that the hydrolysis rate of PEG-SG can be minimized by dissolving in a weakly acidic buffer, such as citrate buffer at pH 4 to about 6 or up to 7, and that the hydrolysis rate decreases as the pH decreases. The most preferred pH is about 4 to less than 5. This is contrary to the earlier view that pH 5.0 to 6.0 is the optimal pH.

[0187] The concentration of the PEG-SG buffer is also significant. The concentration must be high enough to neutralize the changes induced by the acidic NHS released by the PEG-SG due to hydrolysis, but must be low enough not to inhibit the polymerization reaction that occurs once mixed with the PEG-amine solution. Citrate buffer concentrations up to 12.5 mM had no effect on the polymerization time of the lung sealant. However, a higher citrate buffer concentration of 15 mM resulted in an increase in the polymerization time. Citrate buffer concentrations of about 3.5 mM to about 15 mM are preferred, and citrate concentrations of about 5.5 to about 12.5 mM are most preferred.

[0188] The response optimizer algorithm was run to identify the pre-irradiation concentration and pH that would result in an 8 mM citrate buffer with a post-irradiation pH of 4.92. According to this algorithm, a 10.6 mM pre-irradiation citrate buffer (pH = 4.09) would result in a targeted post-irradiation 8 mM buffer (95% confidence interval: 7.89 to 8.11) with a pH = 4.92 (95% confidence interval: 4.91 to 4.93).

[0189] Example 8

[0190] Irradiated FD&C Blue #1 Lung Sealant Colorant

[0191] A 20ug / mL FD&C Blue #1 aqueous solution was gamma irradiated at 32.3kGy-33.1kGy. The absorbance at 628nm was measured for the non-irradiated control and the irradiated samples. The measured absorbances were 2.734 and -0.031, respectively. Due to irradiation, the blue color of the solution was lost. Therefore, the colorant should not be added to the buffer.

[0192] In subsequent preclinical studies, colorants were added to vials containing dry PEG-SG and vials containing dry PEG-amine. FD&C Blue #1 was dissolved in 1 mg / mL ethanol. 120 μl of the liquid was pipetted into each vial (final concentration was 20 ug / mL) and dried overnight in a vacuum oven at room temperature. The PEG was then purged with nitrogen, sealed, and irradiated at 26.9 kGy-27.4 kGy. The blue color was maintained in each dry PEG composition after irradiation. Therefore, it is preferred that FD&C Blue #1 be compounded with a dry PEG composition because color loss occurs when the colorant is irradiated after the colorant is added to the buffer.

[0193] Example 9

[0194] FD&C Blue #1 Irradiation Dosimetry Study

[0195] Significant differences were observed in FD&C Blue #1 concentrations due to X-ray irradiation dose. No differences were observed with doses up to 15 kGy relative to the unirradiated control. A moderate linear correlation was found between X-ray irradiation dose and FD&C Blue #1 concentration, indicating that 6.6 ppm of FD&C Blue #1 was lost for every 1 kGy increase in irradiation dose. Therefore, the colorant should be overdosed by 297 ppm to account for color loss with irradiation doses up to 45 kGy.

[0196] Example 10

[0197] Lung seal efficacy in a physiological isolated lung compartment model

[0198] In an ex vivo physiological lung chamber model, the lung sealing efficacy was tested on porcine lungs. Compared with Mock ProGel, a lung sealing formulation of 28.5 mg / mL 4-arm PEG-amine-10k, 75 mg / mL 4-arm PEG-SG-20k, 50 mM carbonate (pH = 9.0) was tested. This study focused on demonstrating lung sealing efficacy and the application performed, in which the tissue was oriented flat to avoid differences caused by the ability of the sealant to stay in place. Linear soft tissue defects and staple line leaks of 10 mm long and 5 mm deep were formed, resulting in mild to severe leaks. Lung sealant formulations (n ​​= 4) and Mock ProGel (n = 3) showed 100% sealing efficacy at positive pressure ventilator pressures up to 30 cm H2O. Under negative pressure, the lung sealant formulation showed 100% success, but MockProGel failed 33% of linear soft tissue defects and 66% of staple line leaks. Mock ProGel uniquely showed adhesion failure. Although the lung sealant formulation in this example demonstrated 100% sealing efficacy using carbonate buffer, unexpectedly, carbonate buffer is not preferred for use in the lung sealant formulation of the present invention as described herein.Other studies using alkaline buffer and weakly acidic buffer showed unexpectedly superior results.

[0199] Embodiment 11

[0200] Lung seal efficacy in an in vivo model

[0201] The lung sealing efficacy was tested in an acute large animal model. The lung sealing formulations of 62 mg / mL 4-arm PEG-amine-20k (HCl salt), 62 mg / mL 4-arm PEG-SG-20k, 100 mM CHES (pH = 9.4) disclosed herein and the control test product Mock ProGel were tested. A linear soft tissue defect of 12 mm in length and 5 mm in depth and a wedge resection of the left lung lobe apex were performed using an Echelon Flex50 mm linear stapler. A bubble leak test was performed to characterize the severity of air leaks at 20 cm H2O. The formulation was applied using an EVICEL applicator with an Airless Spray Accessory. After completing the pretreatment air leak assessment, the visceral surface of the deflated lung was blotted with dry gauze to remove excess moisture, and then the control Mock ProGel formulation or lung sealant formulation disclosed herein (delivered using a prototype device) was applied to the leak site and staple line. After allowing the control Mock ProGel formulation or lung sealant formulation of the present disclosure to cure for approximately two minutes, the lungs were fully inflated and bubble tested at 20 and 30 cm H2O ventilator pressures to assess initial seal efficacy. The lung sealant of the present disclosure was 100% effective (n=4). Once initial seal efficacy was achieved, the chest wall was temporarily closed using standard techniques. A chest drainage catheter was placed in the pleural space and connected to the Pleur- The drainage system was closed to allow restoration of negative pressure in the chest cavity. After closing the incision, each animal was maintained under anesthesia for approximately 3.5 hours; mechanical ventilation was utilized during this time. The lung sealant formulations of the present disclosure demonstrated 100% sealing efficacy at positive pressure ventilator pressures up to 30 cm H2O (n=4).

[0202] Additives such as chemotherapeutic agents, growth factors, cytokines, antimicrobial agents, procoagulant hemostatic agents, antifibrinolytic agents, and combinations thereof may be delivered in the lung sealants of the present invention.

[0203] It should be understood that certain features of the invention described in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features of the invention described in the context of a single embodiment for simplicity may also be provided separately or in any suitable subcombination or as appropriate in any other described embodiment of the invention. Certain features described in the context of various embodiments should not be considered essential features of those embodiments unless the embodiment does not function without those elements.

[0204] Although various types have been shown and described in this disclosure, additional improvements to the methods and systems described herein may be achieved by those of ordinary skill in the art by appropriate modifications without departing from the scope of the invention. Several such possible modifications have been mentioned, and other modifications will be apparent to those of skill in the art. For example, the examples, types, geometries, materials, dimensions, ratios, steps, etc. discussed above are illustrative and not essential. Therefore, the scope of the present invention should be considered in light of the following claims and should be understood not to be limited to the details of the structure and operation shown and described in the specification and drawings.

Claims

1. A biodegradable lung sealant comprising: a) a first component, the first component comprising a first multi-arm PEG and an alkaline buffer for reconstructing the first multi-arm PEG; b) a second component, wherein the second component comprises a second multi-arm PEG and a weakly acidic buffer for reconstructing the second multi-arm PEG; Wherein, when component (a) and component (b) are combined, they produce an adherent and elastic biodegradable lung sealant.

2. The lung sealant of claim 1, wherein each of the multi-arm PEG of the first component and the multi-arm PEG of the second component further comprises an antioxidant.

3. The lung sealant of claim 2, wherein the antioxidant is tocopherol.

4. The lung sealant of claim 3, wherein the antioxidant is selected from the group consisting of alpha-tocopherol, beta-tocopherol, gamma-tocopherol, delta-tocopherol, tocotrienols, and combinations thereof.

5. The lung sealant of claim 2, wherein the first multi-arm PEG, the second multi-arm PEG, or both the first multi-arm PEG and the second multi-arm PEG further comprise a colorant.

6. The lung sealant of claim 5, wherein the colorant is selected from the group consisting of FD&C Blue #1, FD&C Blue #2, FD&C Green #3, FD&C Yellow #6, and combinations thereof.

7. The lung sealant of claim 1, wherein the first multi-arm PEG and the second multi-arm PEG are each 4-arm PEGs.

8. The lung sealant of claim 1, wherein the first multi-arm PEG is PEG-amine and the second multi-arm PEG is PEG-NHS ester.

9. The lung sealant of claim 8, wherein the PEG-amine is 4-arm PEG-NH2-HCl.

10. The lung sealant of claim 8, wherein the PEG-NHS ester is 4-arm PEG-succinimidyl glutarate (SG).

11. The lung sealant of claim 8, wherein the final concentration of the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester in the lung sealant is each about 39 mg / mL to about 87 mg / mL, and wherein the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester have a molecular weight of 20 kDa.

12. The lung sealant of claim 11, wherein the final concentration of the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester is each about 52 mg / mL to about 77 mg / mL, and wherein the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester have a molecular weight of 20 kDa.

13. The lung sealant of claim 12, wherein the final concentration of the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester is each 67 mg / mL, and wherein the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester have a molecular weight of 20 kDa.

14. The lung sealant of claim 8, wherein the first multi-arm PEG-amine and the second multi-arm PEG-NHS ester are each compounded with about 1500 ppm to about 3000 ppm of an antioxidant.

15. The lung sealant of claim 14, wherein the antioxidant is tocopherol.

16. The lung sealant of claim 9, wherein the pKa of the buffer used to reconstitute the PEG-NH2-HCl is from about 7.9 pKa to about 9.7 pKa.

17. The lung sealant of claim 16, wherein the pKa of the buffer used to reconstitute the PEG-NH2-HCl is from about 8.8 pKa to about 9.4 pKa.

18. The lung sealant of claim 9, wherein the buffer used for the PEG-NH2-HCl has a pH after reconstitution that is at least 0.05 pH units higher than the buffer pKa.

19. The lung sealant of claim 18, wherein the PEG-NH2-HCl has a pH of about 9.0 to about 10.5 after reconstitution.

20. The lung sealant of claim 8, wherein the buffer used to reconstitute the PEG-NHS ester has a concentration of about 3.5 mM to about 15 mM and a pH of about 4.0 to about 7.0 prior to reconstitution.

21. The lung sealant of claim 8, wherein the buffer used to reconstitute the PEG-NHS ester has a pH of about 4.0 to less than 5.0 prior to reconstitution.

22. The lung sealant of claim 8, wherein the first multi-arm PEG is PEG-NH2-HCl and the second multi-arm PEG is 4-arm PEG-SG, and wherein the lung sealant further comprises tocopherol and FD&C Blue #1, and wherein the final concentration of the lung sealant composition after combining the components comprises 67 mg / mL 4-arm PEG-SG (20 kDa), 67 mg / mL 4-arm PEG-NH2-HCl (20 kDa), 340 μg / mL tocopherol, and 80 ug / mL FD&C Blue #1.

23. The lung sealant of claim 1 further comprising a contrast agent.

24. A kit for preparing a biodegradable lung sealant, the kit comprising a first storage container comprising a first multi-arm dry PEG powder and a second storage container comprising an alkaline buffer for preparing the first multi-arm PEG composition; a third storage container comprising a second multi-arm dry PEG powder and a fourth storage container comprising a weakly acidic buffer for preparing the second multi-arm PEG composition; and Wherein the biodegradable lung sealant is formed after combining the first multi-arm PEG composition and the second multi-arm PEG composition and simultaneously applying the first multi-arm PEG composition and the second multi-arm PEG composition to lung tissue.

25. A method of using the lung sealant of claim 8, comprising: adding tocopherol to the 4-arm PEG-amine to form a 4-arm PEG-amine and tocopherol mixture; irradiating the 4-arm PEG-amine and tocopherol mixture; adding a basic buffer to the 4-arm PEG-amine and tocopherol mixture to form a first component of the lung sealant; adding tocopherol to the 4-arm PEG-NHS ester to form a 4-arm PEG-NHS ester and tocopherol mixture; irradiating the 4-arm PEG-NHS ester and tocopherol mixture; adding a weakly acidic buffer to the 4-arm PEG-NHS ester and tocopherol mixture to form a second component of the lung sealant; and mixing the first component and the second component using an application device and simultaneously applying the first component and the second component to lung tissue to form the lung sealant, and allowing the sealant to cure on the tissue.

26. The method of claim 25, wherein the 4-arm PEG-amine and tocopherol mixture and the 4-arm PEG-NHS ester and tocopherol mixture are each irradiated with up to about 40 kilograys (kGy) of X-rays.

27. The method of claim 25, wherein each of the 4-arm PEG-amine and the 4-arm PEG-NHS ester is irradiated under a low oxygen environment and the 4-arm PEG-amine is in a protonated form.

28. A method of preparing a lung sealant, comprising: mixing a basic buffer with the 4-arm PEG-NH2-HCl containing tocopherol to form a 4-arm PEG-NH2-HCl composition; Separately, a weakly acidic buffer is mixed with a 4-arm PEG-SG containing tocopherol to form a 4-arm PEG-SG composition; the 4-arm PEG-NH2-HCl and the 4-arm PEG-SG composition are simultaneously delivered using an application device, wherein the application device allows the 4-arm PEG-NH2-HCl and the 4-arm PEG-SG composition to be fully mixed on the lung tissue; and allowing the lung sealant to cure on the lung tissue.

29. The method of claim 28, wherein the 4-arm PEG-NH2-HCl containing tocopherol is irradiated before mixing with the basic buffer, and the 4-arm PEG-SG containing tocopherol is irradiated before mixing with the weakly acidic buffer.

30. The method of claim 28, further comprising adding 730 ppm to about 3000 ppm of FD&C Blue #1 to the 4-arm PEG-SG, wherein the 4-arm PEG-SG is in dry powder form prior to mixing the 4-arm PEG-SG with the weakly acidic buffer.

31. The method of claim 28, wherein the 4-Arm PEG-NH2-HCl is in the form of a dry powder, and at least about 65% of the 4-Arm PEG-NH2-HCl in the form of the dry powder has a particle size of about 250 microns to about 1250 microns.

32. The method of claim 28, wherein the 4-Arm PEG-NH2-HCl is in the form of a dry powder, and at least about 20% of the 4-Arm PEG-NH2-HCl in the form of the dry powder has a particle size greater than 710 microns.

33. The method of claim 28, wherein the 4-Arm PEG-SG is in the form of a dry powder, and at least about 80% of the 4-Arm PEG-SG in the dry powder form has a particle size of about 250 microns to about 1250 microns.

34. The method of claim 28, wherein the 4-Arm PEG-SG is in the form of a dry powder, and at least about 40% of the 4-Arm PEG-SG in the dry powder form has a particle size greater than 500 microns.

35. The method of claim 28, wherein the pKa of the reconstitution buffer for PEG-NH2-HCl is from about 7.9 pKa to about 9.7 pKa.

36. The method of claim 28, wherein the pH of the buffer for PEG-NH2-HCl after reconstitution is at least 0.05 pH units higher than the buffer pKa.

37. The method of claim 28, wherein the PEG-NH2-HCl composition has a pH of about 9.0 to about 10.5 after reconstitution.

38. The method of claim 28, wherein the reconstitution buffer for PEG-NH2-HCl is an alkaline buffer with a pKa of 9.3, the alkaline buffer having a concentration of about 180 mM to about 220 mM and a pH of about 9.34 to about 9.76 prior to reconstitution.

39. The method of claim 28, wherein the reconstitution buffer for PEG-SG is a weakly acidic buffer having a concentration of about 3.5 mM to about 15 mM and a pH of about 4.0 to about 5.0 prior to reconstitution.